Repensando o planejamento em tempos de globalização e transformações sociais - Guazina, Liziane; Belisário, Kátia Maria (Esferas, 2012)
<!--[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> <!--[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> This article aims to discuss why the concept of planning, usually adopted in the literature of Public Relations, should be critically reconsidered in the light of today’s social and cultural transformations. Globalization, telecommunication development, internet and social networking have changed social relationships and trade, while contributing to the increasing communication crisis. In this context, we should ask: what kind of communication planning can possibly be done in this time of structural transformations? Here we argued that planning should be thought not only from the point of view of traditional theories, but also from the approach of social sciences, particularly Sociology and Anthropology. One cannot forget that it must take into account the diversity of cultures and values ??present in a democracy as informal groups of workers, emergent social classes, civil and social rights movements such as women, homosexuals, ethnical and religious groups and others should be considered, especially in Brazil. In this sense we suggest that it is necessary to consider the other´s perspective when planning, especially when linking new technologies and creativity. Planning, in our view, means more than that. It means making decisions while evaluating and acting upon those decisions, taking into account the perceptions, symbolic interactions and cultural differences that exist among the various groups and situations. It is in times of such social transformations and new technologies that the need to react to events as they unfold will increase to a level of complexity never seen before. Therefore, planning nowadays becomes a form of mobilizing the organization itself in its dialogue with the existing different social groups. <!--EndFragment--> <!--EndFragment-->